Clinical Pathological Outcomes and Survival in Patients Undergoing Surgery for Early Stage Gastric Cancer - Torun, Mehmet; Uzun, Orhan; Gülmez, Selçuk; Senger, Aziz Serkan; Sunar, Ahmet Orhan; Yumak, Merve; Bezir, Nurdan; Polat, Erdal; Duman, Mustafa (Cerrahpaşa Medical Journal, 2025)
Objective: Gastric cancer is the fifth most common cancer worldwide and ranks fourth in cancer-related deaths. Early stage gastric cancer is usually treated with gastrectomy without requiring endoscopic methods or lymph node dissection. This study aims to evaluate the clinicopathological outcomes of early stage gastric cancer among patients undergoing surgery for gastric cancer. Methods: A retrospective analysis was conducted on 340 patients who underwent total or subtotal gastrectomy for gastric cancer at our clinic between February 2007 and September 2019. The clinicopathological features of 32 patients diagnosed with early stage gastric cancer based on histopathological evaluation were analyzed. The final follow-up date was set as December 31, 2022. Results: Early stage gastric cancer was found in 11.3% of all gastric cancer patients. Of these patients, 53.1% were male with a mean age of 61 ± 12 years. The mean tumor size was 2.5 ± 1.4 cm, with no lymph node involvement. Lymphovascular invasion (LVI) and perineural invasion (PNI) were negative in 90.6% of the patients. The mean survival time was 143.6 ± 7.9 months. Conclusion: The clinicopathological outcomes of early stage gastric cancer patients provide promising prognostic insights. The absence of LVI and PNI positively affects the prognosis. The analysis of the 3 deceased patients highlights the impact of high-risk factors. Effective management of postoperative complications can increase morbidity without affecting mortality. Early diagnosis and appropriate surgical treatment in gastric cancer play a critical role in improving long-term survival. These findings emphasize the importance of multidisciplinary approaches and early interventions. Cite this article as: Torun M, Uzun O, Gülmez S, et al. Clinical pathological outcomes and survival in patients undergoing surgery for early stage gastric cancer. Cerrahpaşa Med J 2025; 49, 0052, doi: 10.5152/cjm.2025.24052